Contextualizing Laudato Si’ Responding to the Church’s Role in the Ecological Crisis in Southeast Aceh - Tibo, Paulinus; Bere, Paulus Halek (Indonesian Journal of Advanced Research, 2026)
Ecological issues are not just ordinary problems but global issues that affect grassroots communities that are powerless in terms of knowledge, social, economic, cultural, and religious aspects. The objective is to analyze the presence of religious minority communities in responding to the ecological crisis in Southeast Aceh through the contextualization of ecological theology from the encyclical Laudato Si’, using a qualitative phenomenological approach through interviews and focus group discussions with 26 participants in 2025. The results of the study show the successful implementation of an integral ecology model that transforms reforestation from a technical action into a practice of faith, supported by the synergistic integration of three dimensions: spiritual as a driver of ecological conversion, social through participatory community structures, and technical with sustainable methods such as agroforestry. The main conclusion offers a transformative solution: that addressing the ecological crisis must begin with a transformation of the heart driven by spirituality, strengthened by community, and manifested in systematic concrete actions, while also becoming a blueprint for contextual and value-based environmental conservation. This research contributes to developing a model that promotes social and cultural awareness, as well as ecological conversion, which can be used to create educational curricula from elementary to university levels. Additionally, it serves as a policy recommendation for both the government and the Catholic Church regarding Christian anthropological theology education.